PENGARUH EVENT MARKETING “ERIGO NEW YORK FASHION WEEK 2022” PADA LIVE STREAMING ERIGO X SHOPEE TERHADAP KEPUTUSAN PEMBELIAN ERIGO X DI MARKETPLACE SHOPEE (The Commercium, 2023)
This study aims to examine the effect of Event Marketing "Erigo New York Fashion Week 2022" on Erigo x Shopee Live Streaming on Erigo X purchasing decisions on the Shopee marketplace. This study uses a quantitative approach with an online survey method of followers of Shopee Erigo accounts who have or are considering buying Erigo products. The research samples taken were followers of the official Erigo account on the Shopee platform. Data were analyzed using multiple linear regression to test the hypothesis that the presence of the” Erigo New York Fashion Week 2022” Marketing Event on the Erigo x Shopee Live Streaming has a positive influence on Shopee's purchasing decisions for Erigo X on the Shopee marketplace. The dependent variable in this study is the purchase decision of Erigo X, while the independent variable is the effect of the Erigo New York Fashion Week 2022 Marketing Event on Erigo x Shopee Live Streaming. The results of this study are expected to contribute to understanding the effect of Event Marketing and Livestreaming on product purchasing decisions on the Shopee marketplace. This research can also provide input for companies in developing marketing strategies that are more effective in increasing interest in buying products.